Acts of Taking Other Property Without Permission - Fourus Huznatul Abqoriyyah; Lina Septianasari (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
This research discusses verbs which mean ‘the act of taking other property without permission’ in English. The aims are to (1) describe verb which means ‘the act of taking other property without permission’ in English (2) describe the semantic features of each verb and explain synonym relation among verbs. The data were collected from Cambridge Advance Learner’s Dictionary (2008), Oxford Advanced Learner’s Dictionary (2010), British National Corpus, Corpus of Global Web-Based English, and the explanation of six native speakers by using observation method and teknik catat. The result shows that there are at least forty verbs which mean ‘the act of taking other property without permission’ in English. From componential analysis, found at least seven distinctive semantic features. They are (1) target feature, (2) location feature, (3) manner feature, (4) agent feature, (5) style feature, (6) dialect feature, and (7) usage intensity feature. Synonym relation of each verb shows that different meaning of this research includes four aspects. They are (1) context, (2) style, (3) dialectal, and (4) usage intensity.